2007
DOI: 10.1111/j.1442-2042.2007.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraurethral captopril gel on the recurrence of urethral stricture after direct vision internal urethrotomy: Phase II clinical trial

Abstract: Objective: The purpose of this study is to evaluate the effect of intraurethral captopril gel as an antifibrotic agent on patients with urethral stricture. Materials and Methods: In the first phase of clinical trial, 13 rabbits were included and local side-effects of captopril gel were evaluated. In the second phase, 56 patients were enrolled from April 2004 to January 2006. After internal urethrotomy the patients were classified into three patient groups: (i) received placebo gel (group I); (ii) received 0.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…The angiotensin-converting enzyme inhibitors (ACE-I) can inhibit the angiotensin-converting enzyme and block the conversion of angiotensin I to angiotensin II, thereby reducing angiotensin II levels within the fibrotic tissue, and then reducing TGF-β expression, resulting in an antifibrosis function [15,16,17]. Shiraz et al [1] have reported in patients with urethral stricture, after urethral incision, early administration of ACE-I gel in the urethra could significantly reduce the recurrence rate of urethral stricture. Currently, angiotensin-converting enzyme inhibitors represented by captopril have become an important treatment of congestive heart failure, liver fibrosis, pulmonary fibrosis and other fibrotic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The angiotensin-converting enzyme inhibitors (ACE-I) can inhibit the angiotensin-converting enzyme and block the conversion of angiotensin I to angiotensin II, thereby reducing angiotensin II levels within the fibrotic tissue, and then reducing TGF-β expression, resulting in an antifibrosis function [15,16,17]. Shiraz et al [1] have reported in patients with urethral stricture, after urethral incision, early administration of ACE-I gel in the urethra could significantly reduce the recurrence rate of urethral stricture. Currently, angiotensin-converting enzyme inhibitors represented by captopril have become an important treatment of congestive heart failure, liver fibrosis, pulmonary fibrosis and other fibrotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological examination proved that fibrotic scarring is the major pathological characteristic responsible for upper urinary tract obstruction. For urethra stricture, Shiraz et al [1] have reported that early administration of ACE-I gel in the urethra after urethral incision could significantly reduce the recurrence rate of urethral stricture. However, to our knowledge, up till now, no effective clinical intervention has been found to mitigate or stop such a fibrotic process after ureteral injury.…”
Section: Introductionmentioning
confidence: 99%
“…Based on experience with the antifibrotic properties of the angiotensin-converting enzyme-inhibitor captopril, a phase II clinical trial of intraurethral captopril gel on the recurrence of urethral stricture after OIU/DVIU was conducted [35]. Men 18-79 years old (mean, 39.5 ± 15.3) were followed for 6-30 months (mean, 16).…”
Section: Endoscopic Internal Urethrotomymentioning
confidence: 99%
“…Strictures are associated with alteration of the collagen ratios with a significant increase in type I collagen. 7 To prevent recurrence of strictures, various pharmacologic therapies have been used locally [8][9][10][11] ; however, these substances have not been specific for collagen type I, and therefore, further research into more targeted therapies may produce improvement in outcomes. Halofuginone (HF) is a potent inhibitor of collagen type I 12 and has been demonstrated in previous studies to prevent stricture formation when given systemically.…”
Section: Introductionmentioning
confidence: 99%